(untitled) (RevistAleph, 2022)
The article is a result of a research that addresses the discursive productions generated around education in Uruguay, where there is currently an advance of conservative proposals. Through two initial events some of the discursive logics to be studied are presented. Then the methodological design of the project and the ways in which the methodological approach derives from the conceptual work and the dialogue with previous research are discussed. The methodology and its theoretical underpinning are central to the discussion that the article seeks to elaborate. Finally, some still open debates and reflections are presented. Emphasis is placed on the conservative subjective constructions that are gaining strength with respect to Uruguayan education and on the notion of "educational crisis" that has gained prominence in the public debate and that articulates discursive lines linked to the subject of this research. Key words: conservatism, methodology, systems in disequilibrium, enunciation, education